Comparing email and SNS users: Investigating e-servicescape, customer reviews, trust, loyalty and E-WOM. (March 2020) - Tran, Gina A.; Strutton, David
Abstract: For better or worse, satisfied or dissatisfied customers function as trusted branding faces for organizations as they transmit potentially viral messages through E-WOM. These E-WOM messages can prove marketers' best friends or worst enemies, depending on their tenor. With data from actual customers of an e-tailer, this research enriches our understanding of how e-servicescape is linked to E-WOM. E-servicescape captures the online environmental factors of marketers' websites. Two forms of E-WOM are examined; i.e., emails and social network postings. Customer reviews were investigated as a prospective sub-dimension of e-servicescape. Findings suggest that customer reviews play an integral role in the e-servicescape construct, that e-servicescape positively impacts trust and that trust positively influences E-WOM and customer loyalty. Two groups of customers were compared, and results indicated differences between email and SNS users. Theoretical and managerial insights related to E-WOM and electronic commerce shopping behavior were generated.